Virtual Learning Environments Based on UUM Students Profile for Multi Learning Purposes - Khaleel, Ahmed Isam (2010)
Recently E-learning environment become more useful for presenting and providing learning materials over online services, which has gained significant popularity. E-learning is a multi-dimensional activity where each dimension should be most organization adequately supported by an E-learning system to provide fruitful learning materials to those are interest to read by online, a new experience for most users. The core problem of the current E-learning representation is the formalization of the learning concepts, which form the backbone of knowledge base about the domain or task setting, otherwise the student incapable to practice the different technology to enhance their ability to contribute. Hence, this study aimed to design and develop a virtual learning environment based on the user or student profile. Additionally, the propose system provide users with multi learning materials based on their searching profile. Use test case was adopted in this study for evaluating the system functionalities.